Dampak Pandemi COVID-19 terhadap Tingkat Pengangguran dan Strategi Pemulihan Pasar Tenaga Kerja - Ariana Herawaty; Dwi Rahayu; Alea Naura Ramadhanty; Yahya Amiria Syifaa; Tianata Octia Pasha Hepieni; Muhammad Iqbal Fafallyanuri; Salfa Apriliane (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The COVID-19 pandemic significantly disrupted Indonesia labor market, causing the national unemployment rate to rise from 4,9% in early 2020 to 7,07% by August 2020.Although it declined to 6.49% in 2021, many workers shifted to informal and low-productivity jobs. This shift reflects deeper structural issues such as skill mismatches and high informality. This paper analyzes the pandemic’s impact on unemployment and evaluates key recovery strategies. Based on data from BPS and recent studies. Government responses include the Pre-Employment Card program, aimed at vocational upskilling, and broader reforms like the Job Creation Law. While digital economy growth (e-commerce) offered new opportunities, challenges remain in improving digital skills and job quality. Overall, strengthening job training, promoting inclusive policy reform, and accelerating digital transformation are essential for sustainable labor market recovery in Indonesia.